Effective therapy has altered the spectrum of cause-specific mortality following HIV seroconversion. - Smit, C; Geskus, R; Walker, S; Sabin, C; Coutinho, R; Porter, K; Prins, M (2006)
INTRODUCTION: Although HAART has led to a reduction in overall mortality among HIV-infected individuals, its impact on death from specific causes is unknown. METHODS: Twenty-two cohorts of HIV-infected individuals with known dates of seroconversion are pooled in the CASCADE collaboration. Causes of death (COD) were categorized into three AIDS-related and seven non-AIDS-related causes. The unknown causes were assigned a separate category. The cumulative incidence for each COD was calculated in the presence of the other competing COD, for the pre-HAART and HAART eras. A multivariate regression analyses for the cumulative rate of progression to the different COD was performed. RESULTS: A total of 1938 of 7680 HIV-seroconverters died. Pre-HAART, AIDS opportunistic infections (OI) was the most common COD, followed by unknown and HIV/AIDS-unspecified. In the HAART era, the cumulative incidence for all AIDS-related COD decreased, OI remaining the most important. Large reductions in death due to other infections and organ failure were seen. Cumulative death risk decreased in the HAART era for most causes. The effect of HAART was not the same for all risk groups. The cumulative risk of death from AIDS-related malignancies, OI and non-AIDS-related malignancies decreased significantly among homosexual men (MSM), whereas the risk of dying from (un)-intentional death increased significantly among injecting drug users (IDU). A non-significant increase in hepatitis/liver-related death was seen in MSM, IDU and haemophiliacs. CONCLUSION: Overall and cause specific mortality decreased following the introduction of HAART. OI remain the most common COD in the HAART era, suggesting that AIDS-related events will continue to be important in the future. Future trends in COD should be monitored using standardized guidelines.